2015
DOI: 10.1007/s00383-015-3850-5
|View full text |Cite
|
Sign up to set email alerts
|

Omental acinar cell carcinoma of pancreatic origin in a child: a clinicopathological rarity

Abstract: A 6-year-old boy presented with a large subhepatic mass associated with pain abdomen. Exploration revealed a tumor in lesser omentum, completely separate from the normal pancreas that was excised completely. Histopathology suggested acinar cell carcinoma of pancreatic origin in an ectopic location. The child is well at 5 months follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Heterotopic tissue may cause symptoms related to mechanical complications, such as gastric outlet obstruction [9] or intussusception [21, 22]; in other circumstances, heterotopic pancreatic tissue may cause bleeding from the surrounding intestinal mucosa [23]. Occasionally, metaplastic changes may occur in heterotopic tissue, leading to the development of malignancy in adulthood [5, 24, 25]; even though exceedingly rare, malignancies arising from heterotopic pancreas have been described also in children [2628]. In our series, 7 out of 14 patients (50%) had symptoms related to the presence of heterotopic pancreas; presenting complaint were recurrent vomiting, dyspepsia, intussusception, bleeding and recurrent abdominal pain.…”
Section: Discussionmentioning
confidence: 99%
“…Heterotopic tissue may cause symptoms related to mechanical complications, such as gastric outlet obstruction [9] or intussusception [21, 22]; in other circumstances, heterotopic pancreatic tissue may cause bleeding from the surrounding intestinal mucosa [23]. Occasionally, metaplastic changes may occur in heterotopic tissue, leading to the development of malignancy in adulthood [5, 24, 25]; even though exceedingly rare, malignancies arising from heterotopic pancreas have been described also in children [2628]. In our series, 7 out of 14 patients (50%) had symptoms related to the presence of heterotopic pancreas; presenting complaint were recurrent vomiting, dyspepsia, intussusception, bleeding and recurrent abdominal pain.…”
Section: Discussionmentioning
confidence: 99%
“…When symptomatic It can present as intestinal bleeding, obstruction, intussusception, or malignant transformation. [7][8][9] The etiology is unclear, several theories have been proposed. One mentions that the embryonic cells could be transported to adjacent structures during the bowel axial rotation, which would certainly explain the described locations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Dall'igna et al [6] reviewed 21 patients aged 18 years or younger with pancreatic tumors reported in Italy between 2000 and 2009, including 2 cases of ACC. Table 2 summarizes the 26 reported pediatric cases, including the patients from the above reports and our case [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Although the details are often unclear, the following characteristics of pediatric ACC can be suggested: (1) the tumors tend to be very large at diagnosis, (2) distant metastasis is rare and in most cases lesions are (9).…”
Section: Discussionmentioning
confidence: 99%